Multivariate analysis techniques in social science research : from problem to analysis - Tacq, Jacques (Sage, 1997)
acq demonstrates how a researcher comes to the appropriate choice of a technique for multivariate analysis. He examines a wide selection of topics from a range of disciplines including sociology, psychology, economics, and political science